1999
DOI: 10.1039/a808958b
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol condensed phases Part I. A molecular dynamics study

Abstract: Using a model potential function we have performed a molecular dynamics simulation of several static and dynamical properties of glycerol in the crystal, glass and liquid phases. Comparison with available experimental data shows an excellent agreeent and proves the validity of the potential model used. For the calculation of the molar speciÐc heat of the liquid and of the glass we have developed a theoretical approach which takes into account the contributions of the conformational structure energy and of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
133
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(146 citation statements)
references
References 41 publications
9
133
1
3
Order By: Relevance
“…Chelli et al have performed a molecular dynamics (MD) simulation for glycerol. They reported that there are large clusters of glycerol molecules connected through hydrogen bonds, and that the lifetime of these clusters is strongly correlated with diffusion time [21]. On the basis of this network picture, our experimental result suggests that the topology of the hydrogen-bonding network (coordination number) plays a key role in the glass transition of a hydrogen-bonding liquid.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Chelli et al have performed a molecular dynamics (MD) simulation for glycerol. They reported that there are large clusters of glycerol molecules connected through hydrogen bonds, and that the lifetime of these clusters is strongly correlated with diffusion time [21]. On the basis of this network picture, our experimental result suggests that the topology of the hydrogen-bonding network (coordination number) plays a key role in the glass transition of a hydrogen-bonding liquid.…”
Section: Resultsmentioning
confidence: 56%
“…Although such composition dependence of coordination number is frequently discussed for covalent network glasses, the temperature dependence is rarely discussed. On the other hand, in hydrogen-bondingnetwork glasses, the probability for hydrogen-bonding formation depends significantly on temperature, as shown by MD simulation [21]. Therefore, the mean coordination number of a hydrogen-bonding molecule is also dependent on temperature, and cannot be fixed at any given value.…”
Section: Resultsmentioning
confidence: 99%
“…In crystals an extended structure with backbone torsion angles close to 180°has been found and justified theoretically, similarly as for other polyhydroxy compounds. 16 However, controversial theoretical and experimental models have been proposed for the liquid phase, mostly suggesting a large conformational flexibility. [16][17][18][19][20][21] Almost free rotation of the hydroxyl groups (between the three preferable staggered positions) was predicted for the glycerol molecule, which is in many aspects similar to the gluconate.…”
Section: Introductionmentioning
confidence: 99%
“…16 However, controversial theoretical and experimental models have been proposed for the liquid phase, mostly suggesting a large conformational flexibility. [16][17][18][19][20][21] Almost free rotation of the hydroxyl groups (between the three preferable staggered positions) was predicted for the glycerol molecule, which is in many aspects similar to the gluconate. 22 The high degree of flexibility also best corresponds to the results presented below.…”
Section: Introductionmentioning
confidence: 99%
“…For PTFE and others fluorinated polymers it is well known that surface properties, in particular SFE, are related with weak molecular forces and the existence of C-F bonds from CF 2 groups [16,17]. The properties of these surfaces depend not only on the coverage by the fluorocarbons but also on the degree of order of the surface [18,19].…”
Section: A Linear Dependence Betweenmentioning
confidence: 99%